Cardiac Nav1.5 is modulated by ubiquitin protein ligase E3 component n‐recognin UBR3 and 6. Issue 9 (7th June 2015) - Zhao, Chunxia; Wang, Lijie; Ma, Xiue; Zhu, Weidong; Yao, Lei; Cui, Yingyu; Liu, Yi; Li, Jun; Liang, Xingqun; Sun, Yunfu; Li, Li; Chen, Yi‐Han
Abstract: The voltage‐gated Na + channel Nav 1.5 is essential for action potential (AP) formation and electrophysiological homoeostasis in the heart. The ubiquitin–proteasome system (UPS) is a major degradative system for intracellular proteins including ion channels. The ubiquitin protein ligase E3 component N‐recognin (UBR) family is a part of the UPS; however, their roles in regulating cardiac Nav 1.5 channels remain elusive. Here, we found that all of the UBR members were expressed in cardiomyocytes. Individual knockdown of UBR3 or UBR6, but not of other UBR members, significantly increased Nav 1.5 protein levels in neonatal rat ventricular myocytes, and this effect was verified in HEK293T cells expressing Nav 1.5 channels. The UBR3/6‐dependent regulation of Nav 1.5 channels was not transcriptionally mediated, and pharmacological inhibition of protein biosynthesis failed to counteract the increase in Nav 1.5 protein caused by UBR3/6 reduction, suggesting a degradative modulation of UBR3/6 on Nav 1.5. Furthermore, the effects of UBR3/6 knockdown on Nav 1.5 proteins were abolished under the inhibition of proteasome activity, and UBR3/6 knockdown reduced Nav 1.5 ubiquitylation. The double UBR3–UBR6 knockdown resulted in comparable increases in Nav 1.5 proteins to that observed for single knockdown of either UBR3 or UBR6. Electrophysiological recordings showed that UBR3/6 reduction‐mediated increase in Nav 1.5 protein enhanced the opening of Nav 1.5 channels and thereby the amplitude of the AP. Thus, our findings indicate that UBR3/6 regulate cardiomyocyte Nav 1.5 channel protein levels via the ubiquitin–proteasome pathway. It is likely that UBR3/6 have the potential to be a therapeutic target for cardiac arrhythmias.